Regulation of Enteric Infection and Immunity by Dietary Proanthocyanidins - Andersen-Civil, Audrey I. S.; Arora, Pankaj; Williams, Andrew R. (Frontiers in Immunology, 2021)
The role of dietary components in immune function has acquired considerable attention in recent years. An important focus area is to unravel the role of bioactive dietary compounds in relation to enteric disease and their impact on gut mucosal immunity. Proanthocyanidins (PAC) are among the most common and most consumed dietary polyphenols, and are characterised by their variable molecular structures and diverse bioactivities. In particular, their anti-oxidative effects and ability to modulate gut microbiota have been widely described. However, there is limited evidence on the mechanism of action of PAC on the immune system, nor is it clearly established how PAC may influence susceptibility to enteric infections. Establishing the sites of action of PAC and their metabolites within the gut environment is fundamental to determine the applicability of PAC against enteric pathogens. Some mechanistic studies have shown that PAC have direct modulatory effects on immune cell signalling, isolated pathogens, and gut mucosal barrier integrity. Boosting the recruitment of immune cells and suppressing the amount of pro-inflammatory cytokines are modulating factors regulated by PAC, and can either be beneficial or detrimental in the course of re-establishing gut homeostasis. Herein, we review how PAC may alter distinct immune responses towards enteric bacterial, viral and parasitic infections, and how the modulation of gut microbiota may act as a mediating factor. Furthermore, we discuss how future studies could help unravel the role of PAC in preventing and/or alleviating intestinal inflammation and dysbiosis caused by enteric disease.